Changes in Hemodynamic Indications after Myocardial Infarction - Sunnatova, G. I; Tursunboev, H. S (American Journal of Bioscience and Clinical Integrity, 2024)
Diseases of the cardiovascular system are currently the most pressing problem of modern medicine and domestic healthcare. The leading causes of death associated with cardiac dysfunction are progressive chronic heart failure (CHF) and sudden cardiac death (SCD). Based on statistics for Russia, about 250-300 thousand people die from SCD every year. In patients who have suffered a myocardial infarction (MI), heart failure (HF) is caused by a decrease in the pumping function of the heart when a significant portion of the myocardium is activated from contraction. Impaired pumping function of the left ventricle of the heart without clinical signs of HF or with minimal or pronounced manifestations, in our opinion, should be considered in terms of hemodynamic supply to the left ventricles (LV). The New York Heart Association has developed a classification of heart failure into class IV (Stages). At the same time, identifying circulatory decompensation taking into account clinical and angiographic signs is important for assessing the condition of patients and selecting drug therapy. And also, when developing indications for surgical correction of this complication.